Tingkat Adopsi Teknologi Pemupukan Urea Plus Karbofuran 3g (Pupk3g) pada Persemaian Tanaman Padi Sawah (Oryza Sativa) - Dahlan, Rohib; Sulaksana, Jaka; Dinar, Dinar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the adoption rate of Urea Plus Carbofuran 3G (PUPK3G) fertilization technology in rice (Oryza sativa) seedlings and the factors that influence the adoption rate. The low adoption rate of PUPK3G and the factors that influence the adoption rate of technology can inhibit the increase in the adoption rate of technology and the factors that support and inhibit the adoption rate of technology need to be supported with the aim of increasing the adoption of PUPK3G and increasing the factors that influence the adoption rate of technology both internal and external factors. The research method used is a quantitative descriptive survey with data collection through questionnaires and interviews with farmers who use and do not use PUPK3G technology in the research area. Adoption of innovation is a process of changing behavior, both knowledge (cognitive), attitude (affective), and skills (psychomotor) in a person since they are introduced to the innovation (Rogers and Shoemaker, 1971 in Ediset, 2021) aims to increase the adoption rate according to the level of awareness, assessment, analysis, trial and adoption. The results of the study indicate that the adoption rate of PUPK3G technology is in the high category, with the indicator that influences the highest adoption rate in the aspect of the length of farming, while the lowest indicator that influences the adoption rate of technology is in the aspect of farmer education. The conclusion in the study resulted in a technology adoption rate of 62% in the high category influenced by factors that influence technology by 72% and the results of the regression coefficient positive direction of 0.785 shows a significant increase in the level of adoption of PUPK3G technology which has an impact on the implications and recommendations that PUPK3G technology needs to be widely improved to increase production and efficiency.